LncRNA MBNL1-AS1 represses gastric cancer progression via the TGF-β pathway by modulating miR-424-5p/Smad7 axis. Issue 3 (1st March 2022) - Su, Jiewen; Chen, Dawei; Ruan, Yi; Tian, Yuan; Lv, Kaiji; Zhou, Xinhua; Ying, Dongjian; Lu, Yeting
ABSTRACT: Studies over the past decades have implicated lncRNAs in promoting the development, migration and invasion of gastric cancer (GC). However, the role and mechanism of lncRNA MBNL1-AS1 in GC promotion are poorly understood. In this research, qRT-PCR showed that MBNL1-AS1 was down-regulated in GC tissues and cells. Cell experiments and the animal study demonstrated that MBNL1-AS1 knockdown accelerated GC cell proliferation, migration, and invasion, thus restraining cell apoptosis. Meanwhile, overexpression of MBNL1-AS1 repressed GC cell promotion. Bioinformatics analysis confirmed that MBNL1-AS1 binds to miR-424-5p via negative modulation. Rescue experiments showed that decreased miR-424-5p level inhibited GC cell promotion by silencing MBNL1-AS1. Furthermore, Smad7 was identified as a target of miR-424-5p that could reverse the promotion of GC cell growth mediated by miR-424-5p. Western blot results proved that MBNL1-AS1 affected TGF-β/SMAD pathways by regulating the miR-424-5p/Smad7 axis. Collectively, MBNL1-AS1 restrained GC growth via the miR-424-5p/Smad7 axis and thus could be a promising target for GC therapy. These findings illustrate that lncRNA MBNL1-AS1, as a tumor suppressor gene, participates in GC progression by regulating miR-424-5p/Smad7 axis, thus activating TGF-β/EMT pathways. The evidence may provide a potential marker for GC patients. Graphical abstract: uf0001